KESULITAN SISWA SEKOLAH DASAR DALAM MEMAHAMI KONSEP MATEMATIKA - Hajjah Rafiah (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
The learning difficulties presented by students indicated something was wrong. Errors can be in the form of mistakes in understanding the concept, forgetting the completion procedure, or mistakes because there is no thoroughness. Therefore, the purpose of this study was to describe the difficulties students have in understanding mathematical concepts. This research was conducted using a qualitative approach. The subjects in this study were basic school students of class VA SDN Teluk Tiram 2 Banjarmasin in the 2018/2019 academic year. The instruments used in this study were test questions and new interviews. The results showed that the difficulties faced by elementary school students in understanding mathematical concepts, namely the material of numbers and geometry, occurred because students did not understand concepts from the start, lacked prerequisite knowledge, were not careful in the computational process, and forgot the completion procedure.